Peran Islam dalam masyarakat Indonesia: Agama dan sistem kebudayaan yang berintegrasi - Nabila, Sania; Ghozi, Ahmad; Nengkaton, Wahyu; Citra, Najwa Naila Kharisma (Maliki Interdisciplinary Journal, 2024)
Islam is a universal, perfect, flexible, and adaptive religion, covering all aspects of human life, including social and political fields. The Islamic Shari'a brought by the Prophet Muhammad (PBUH) provides guidance capable of bringing humanity from darkness to the light of faith. The relationship between religion, culture and society is mutually influential, having a significant impact on ethics, architecture, social structure and customs. Islam influences culture and society, but culture can also change the interpretation of religion. In Indonesia, Islamic culture has merged with local culture, resulting in a unique and ongoing acculturation. Islam distinguishes between worship (which is definitive and comprehensive) and muamalah (basic principles that evolve over time). Islamic culture covers various aspects of life and encourages its adherents to contribute positively to the development of civilization. The importance of the history of Islamic civilization must be recognized as it helps to foster attachment to Islamic culture, recognize the work of scholars, increase the responsibility of Muslim generations, and draw lessons from the past. In Indonesia, Islam developed with respect for local culture and contributed to the philosophy of life of the people, such as Pancasila. Islam and local culture support and strengthen each other, creating a diverse yet harmonious society. From a sociological point of view, religion plays an important role in maintaining the integrity of society through social solidarity and integration. True religion provides freedom and guidance to develop human potential to the fullest. The reciprocal relationship between religion and culture shows that both influence each other and contribute to human social and spiritual development. A person who is sincere in religion will respect and love others, live a harmonious life and appreciate differences as a gift from Allah SWT.